1998
DOI: 10.1590/s0004-282x1998000200025
|View full text |Cite
|
Sign up to set email alerts
|

Compressão medular torácica em dois níveis por calcificação de ligamento amarelo: relato de caso

Abstract: RESUMO -Calcificação e/ou ossificação do ligamento amarelo é patologia bem conhecida na literatura japonesa. Causa estenose do canal vertebral torácico e compressão medular. Os autores apresentam o caso de um paciente de origem não japonesa com mielopatia torácica causada por compressão devida a calcificação do ligamento amarelo.PALAVRAS-CHAVES: medula torácica, mielopatia, ligamento amarelo, compressão medular.Thoracic spinal cord compression at two levels due to ligamentum flavum calcification: case report A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
11
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 14 publications
3
11
0
Order By: Relevance
“…Ossification of the ligamentum flavum (OLF) is an uncommon cause for thoracic myelopathy which demands surgical treatment. This condition usually is described in Far East countries, fairly common in Japanese people 1 , even though rare in Western countries [2][3][4][5] . Two cases were reported in Brazil 4,5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ossification of the ligamentum flavum (OLF) is an uncommon cause for thoracic myelopathy which demands surgical treatment. This condition usually is described in Far East countries, fairly common in Japanese people 1 , even though rare in Western countries [2][3][4][5] . Two cases were reported in Brazil 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…This condition usually is described in Far East countries, fairly common in Japanese people 1 , even though rare in Western countries [2][3][4][5] . Two cases were reported in Brazil 4,5 . Polgar was the first to describe OLF, in 1929 6 , and Yamaguchi et al 7 , in 1960, reported the first case of OLF causing thoracic myelopathy.…”
Section: Introductionmentioning
confidence: 99%
“…However, that disorder is extremely rare in Western populations, in which only cervical and lumbar degenerative myelopathies or radiculopathies are commonly found. 1 Most of the pathophysiological mechanisms of that condition and reasons for its peculiar prevalence in Eastern countries are unknown. Hypertrophy of the spinal ligaments might begin in response to mechanical stress, but in patients with genetic or systemic predisposing factors, that process progresses with ligament hyperplasia, vascular neoformation, cartilaginous metaplasia, calcifi cation, and, eventually, replacement by compact bone.…”
Section: Introductionmentioning
confidence: 99%
“…In cases of hypertrophy, the normal fibrous structure of the ligamentum flavum is replaced by hypertrophic fibrous tissue containing numerous fibrocartilaginous cells with abundant matrix 9 . Such calcification consists of thickening of the deep layers of the LF, whereas the corresponding ossification affects only the most superficial layers 10. Ossification or calcification of the ligamentum flavum is an idiopathic endochondral calcification that affects approximately 20% of individuals who are of Eastern origin and who are older than 60 years of age 11 , being rare in those who are not of Eastern origin and in those who are younger than 50 years. Ossification or calcification of the ligamentum flavum can be associated with Paget's disease, rickets, chondrocalcinosis, ankylosing spondylitis, hypoparathyroidism, skeletal hyperostosis, obesity, diabetes, hyperinsulinemia, and disorders of calcium metabolism 11 .…”
mentioning
confidence: 99%
“…A CT scan can reveal a calcified/ ossified extradural mass located under the vertebral lamina and protruding into the intervertebral foramen, with a loss of extradural fat 11. In determining the degree of spinal cord compression and the characteristics of ossification, MRI is extremely useful, the ligamentum flavum appearing hypointense on T1-and T2-weighted images. The typical indentation is best seen on T2-weighted images 11 .The use of CT and MRI in combination provides information that is more accurate and useful for treatment planning than does the use of either alone [4][5][6][7][8][9] .…”
mentioning
confidence: 99%